Alcam Regulates Long‐Term Hematopoietic Stem Cell Engraftment and Self‐Renewal123. (25th February 2013) - Jeannet, Robin; Cai, Qi; Liu, Hongjun; Vu, Hieu; Kuo, Ya‐Huei
Abstract Hematopoietic stem cells (HSCs) reside in a specialized bone marrow (BM) microenvironment that supports the maintenance and functional integrity of long‐term (LT)‐HSCs throughout postnatal life. The objective of this work is to study the role of activated leukocyte cell adhesion molecule (Alcam) in HSC differentiation and self‐renewal using an Alcam‐null (Alcam−/−) mouse model. We show here that Alcam is differentially regulated in adult hematopoiesis and is highly expressed in LT‐HSCs where its level progressively increases with age. Young adult Alcam−/− mice had normal homeostatic hematopoiesis and normal numbers of phenotypic HSCs. However, Alcam−/− HSCs had reduced long‐term replating capacity in vitro and reduced long‐term engraftment potential upon transplantation. We show that Alcam−/− BM contain a markedly lower frequency of long‐term repopulating cells than wild type. Further, the long‐term repopulating potential and engraftment efficiency of Alcam−/− LT‐HSCs was greatly compromised despite a progressive increase in phenotypic LT‐HSC numbers during long‐term serial transplantation. In addition, an age‐associated increase in phenotypic LT‐HSC cellularity was observed in Alcam−/− mice. This increase was predominately within the CD150hi fraction and was accompanied by significantly reduced leukocyte output. Consistent with an aging‐like phenotype, older Alcam−/− LT‐HSCs display myeloid‐biased repopulation activity upon transplantation. Finally, Alcam−/− LT‐HSCs display premature elevation of age‐associated gene expression, including Selp, Clu, Cdc42, and Foxo3. Together, this study indicates that Alcam regulates functional integrity and self‐renewal of LT‐HSCs. STEM CELLS2013;31:560–571